Letopis Fakultete za gradbeništvo, prometno inženirstvo in arhitekturo 2021/2022 (University of Maribor Press, 2022)
Yearbook Faculty of Civil Engineering, Transportation Engineering and Architecture 2021/2022. The publication provides an overview of the faculty’s achievements in the academic year 2021/22. It briefly presents the activities and study programs conducted at the faculty, namely Civil Engineering, Industrial Engineering, Traffic and Transportation Engineering, and Architecture. Additionaly best publications, projects, field trips, workshops, exhibitions, as well as the work of the Student Council and Alumni Club of FGPA are also presented. All diploma, master and doctoral theses of the academic year 2021/22 are included. First reprint of first edition, 30 1. 2023.